The Australian Historic Shipwreck Preservation Project: In situ Preservation and Long-Term Monitoring of the Clarence (1850) and James Matthews (1841) Shipwreck Sites. (2nd July 2016) - Richards, Vicki; MacLeod, Ian; Veth, Peter
Abstract : Increasingly, archaeologists are opting for on-site examination, reinterment, and in situ preservation of underwater cultural heritage sites as the first option in the management of sites at risk, as opposed to the more traditional excavation, recovery, conservation, and display/storage methods. This decision will inevitably be based on significance assessment, degree of perceived risk, and resourcing issues. However, long-term monitoring must become an integral part of these management programmes in order to quantitatively evaluate the effectiveness of the in situ preservation techniques employed. In 2012 the Australian Historic Shipwreck Preservation Project (AHSPP) was awarded a large Australian Research Council (ARC) Linkage Grant, enabling ten partner organizations and three Australian universities to collaborate in one of the largest multi-organizational maritime archaeology projects to be undertaken in Australia to date. One of the major aims of the project is to develop a protocol for the excavation, detailed recording and reburial of significant shipwrecks under threat, fostering a strategic national approach for the management of underwater cultural heritage (UCH) sites at risk. Two historically significant shipwreck sites that are considered under threat were chosen for this longitudinal comparative study — the Clarence (1850) located in Port Phillip Bay, Victoria; and the James Matthews (1841) which lies in Cockburn Sound, Western Australia. Both sites have been preserved in situ using two very different but innovative remediation strategies. More importantly, long-term monitoring programmes have been implemented on both sites, which will characterize changes in the reburial environment and the effect on the reinterred materials. In this way, the efficacy of both in situ preservation techniques will be systematically tested, providing a comparative analysis of practical protocols for the long-term protection and management of underwater cultural heritage.